Novel Radiation Facilities Based on Plasma Acceleration: The Future of Free Electron Lasers - Marcello Coreno; Massimo Ferrario; Augusto Marcelli; Francesco Stellato (Condensed Matter)
Exploiting acceleration gradients that are up to three orders of magnitude higher than those achievable using conventional radiofrequency-based devices, plasma-based devices promise a revolution in particle acceleration, enabling particles to reach high energies over much shorter distances than existing accelerators [...]